Bahasa Rupa Relief Cerita Kresnayana Candi Prambanan - Deni Iskandar, Asep; Supandi, Fajar Persada (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
The Kresnayana story relief in the Prambanan temple complex is considered by researchers as a past artifact that can provide information. The information presented is in the form of visuals that tell the Kresnayana epic. The Kresnayana story relief is a transformation of a literature (kitab) originating from India. The carvers select the scene in the most appropriate paragraph, then visualize and arrange the composition of each image in each panel. The selected scenes in each panel are then assembled into a complete Kresnayana story. In a modern visual context, the series of scenes arranged into a unified story is like a movie. In order to depict all the scenes within the limited picture plane, the sculptors used a typical drawing method with the space-time-flat system. The way of drawing done by the carvers is very different from the modern Western way of drawing. The distinctive way of drawing on each relief panel is then considered to be strange and makes it difficult to read the story scene. This way of drawing is used to examine the reliefs of the Kresnayana story. This research uses descriptive and qualitative methods. How to draw space-time-flat needs to be analyzed so that it can be utilized in the process of working on various media. How to draw space-time-flat needs to be analyzed so that it can be utilized in the process of creating works in various visual media. From the results of the analysis, information on the typical drawing method that was used before the discovery of the Western drawing method with the naturalist-perspective-moment opname system can be found.